Women make horror : filmmaking, feminism, genre - Peirse, Alison (Rutgers University Press, 2020)
"Women Make Horror is the first book-length study of women filmmakers in horror film, the first all-women edited book on horror film, and the first book to call out the male-bias in written histories of horror and then to illuminate precisely how, and where, these histories are lacking. It re-evaluates existing literature on the history of horror film, on women practitioners in the film industry and approaches to undertaking film industries research. It establishes new approaches for studying women practitioners and illuminates their unexamined contribution to the formation and evolution of the horror genre. The book focuses on women directors and screenwriters but also acknowledges the importance of women producers, editors and cinematographers. It explores narrative and experimental cinema, short, anthology and feature-filmmaking, and offers case studies of North American, Latin American, European, East Asian and Australian filmmakers, films and festivals. With this book we can transform how we think about women filmmakers and genre"--